Issue Information. Issue 6 (12th November 2020) - Hawk, J.L.M.
Abstract : The cover image is based on the Review Article Safe, mild ultraviolet‐B exposure: An essential human requirement for vitamin D and other vital bodily parameter adequacy: A review by J.L.M. Hawk https://doi.org/10.1111/phpp.12584 . ImageCredit: From Holick et al, (1981) J Invest Dermatol 76:51‐58. Reprinted with permission from AAAS.